2015
DOI: 10.1111/jan.12681
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with relational coordination between health professionals involved in insulin initiation in the general practice setting for people with type 2 diabetes

Abstract: An expanded role and experience of practice nurses in diabetes care increased relational coordination and has the potential to deliver more effective chronic disease management in general practice. Practice and health professional characteristics should be taken into account when designing models of care to increase insulin initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Our study recommendations are consistent with relational coordination theory and a growing number of studies in multiple sectors showing that human resource practices are a significant driver of relational coordination and associated performance outcomes, for better or worse depending on their design [e.g., (22,38,(49)(50)(51)]. Our recommendations also build on our findings that it may be possible to intentionally improve relationships between direct care staff and the community through low cost, replicable interventions.…”
Section: Supporting Relationship-centered Care Through Human Resource...supporting
confidence: 83%
“…Our study recommendations are consistent with relational coordination theory and a growing number of studies in multiple sectors showing that human resource practices are a significant driver of relational coordination and associated performance outcomes, for better or worse depending on their design [e.g., (22,38,(49)(50)(51)]. Our recommendations also build on our findings that it may be possible to intentionally improve relationships between direct care staff and the community through low cost, replicable interventions.…”
Section: Supporting Relationship-centered Care Through Human Resource...supporting
confidence: 83%
“…While this systematic review has revealed many insights about building relational coordination across occupational diversity, the challenge of building relational coordination across demographic diversity is a more recent area of focus. One study in our review found that female physicians experienced significantly lower levels of relational coordination from their colleagues than did male physicians (Manski-Nankervis et al, 2015), while another found that relational coordination was significantly stronger in interprofessional teams with a higher percentage of women (Hustoft et al, 2018). H. W. Lee and Kim (2019) were the first to systematically incorporate demographic diversity into relational coordination theory, proposing that demographic diversity tends to weaken relational coordination due to a reduction in social cohesion.…”
Section: Building Relational Coordination In a Diverse Workforcementioning
confidence: 84%